The Association of Individual Factors and Organization Culture and Approach with Nursing Quality of Care in Ganesha Public Hospital, Gianyar - I Gusti A. Ayu Sherlyna Prihandhani; Ni Made Sri Nopiyani; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2015)
Background and purpose: Satisfaction survey among patients of the inpatient unit at Ganesha Public Hospital indicated lack of caring behavior among nurses. This study aims to reveal level of quality of care and the factors associated with related behavior among inpatient ward at Ganesha Public Hospital. Methods: The study used cross-sectional survey design. Data were collected through self-administered questionnaires among 48 inpatient nurses during November-December 2014. Multivariate logistic regression was applied to determine factors associated with caring behavior of nurses. Results: The study found that 56.3% believed they provided a relatively high quality of care and 54,2% of nurses indicated a positive perception of the organization culture. Result of multivariate analysis indicated that only rewards system is independently associated with caring behavior of nurses (adjusted OR=23,39; 95%CI: 1.53-356.94; p=0,023). Conclusion: It was evident that nurses’ practice toward caring behavior is related to their attitude toward the rewards system of nurses’ performance.